Konjenital adrenal hiperplazi olgularımızın enzim eksikliği açısından dağılımı: Yüz kırk beş hasta ile tek merkez deneyimi - Yıldız, Melek; Önal, Hasan; Aydın, Banu; Gezdirici, Alper; Akgün, Abdurrahman; Yılmaz Güleç, Elif; Belde Doğan, Beyza; Adal, Erdal (Logos Tıp Yayıncılık, 2019)
Amaç: Konjenital adrenal hiperplazi (KAH), adrenal steroidogenez basamaklarından birinde gerçekleşen, enzim eksikliği nedeniyle ortaya çıkan, otozomal resesif geçişli genetik bir hastalıktır. En sık nedeni 21-hidroksilaz eksikliğidir. Bu çalışmada, bölümümüzde takipli KAH tanılı hastaların enzim eksikliği açısından dağılımlarının belirlenmesi ve klinik özelliklerinin ortaya konulması amaçlanmıştır. Yöntem: Ocak 1998-Ocak 2018 tarihleri arasında KAH tanısı alarak kliniğimizde izlenmiş olan 145 hastanın dosyası retrospektif olarak incelendi. Olguların başvuru yaşı, başvuru yakınması, cinsiyeti, izlemde puberte prekoks ve hipertansiyon gelişimi, testiküler adrenal rest tümör varlığı, hormonal değerlendirmeleri ve klinik tanıları kaydedildi. Bulgular: Çalışmaya 82 kız, 63 erkek hasta alındı. Bütün hastalar genetik cinsiyetlerine uygun yetiştirilmişti. Hastaların %87,6’sı 21-hidroksilaz eksikliği olup, bunların %80,9’u klasik (%76,3’ü tuz kaybettiren tip, %23,7’si basit virilizan tip), %19,1’i ise non-klasik (geç başlangıçlı) tip idi. Olguların %9,0’ı 11?hidroksilaz eksikliği, %2,8’i 3?-hidroksisteroid dehidrogenaz eksikliği, %0,7’si ise POR eksikliği idi. Olguların %73,8’inde akraba evliliği mevcuttu. Kız hastaların %70,7’si kuşkulu genital yapı ile erkek hastaların %73,0’ı ise tuz kaybı ile tanı almıştı. On beş hasta santral puberte prekoks nedeniyle GnRH analoğu kullanmıştı. Erkek olguların %14,3’ünde testiküler adrenal rest tümör, kız olguların %9,8’inde polikistik over sendromu mevcuttu. 11?-hidroksilaz eksikliği olgularının yaklaşık yarısında hipertansiyon mevcuttu. POR eksikliği saptanan tek hastaya sendromik özelliklerinden dolayı Antley-Bixler sendromu tanısı konulmuştu. Sonuç: Merkezimizdeki KAH hastalarında gözlenen enzim eksikliği dağılımı literatür ile uyumlu bulunmuştur. 21-hidroksilaz eksikliği açısından mutasyon saptanmayan, hipertansiyon ve sendromik görünüm benzeri klinik özellikleri bulunan ve hormonal açıdan ipucu olan hastalar nadir KAH formları açısından değerlendirilmelidir.

Objective: Congenital adrenal hyperplasia (CAH) is an autosomal recessive disorder caused by a defect in any of the enzymatic steps of adrenal steroidogenesis. The most common cause is the 21-hydroxylase deficiency. In this study, we aimed to determine the distribution of the patients with diagnosis of CAH who were followed up in our clinic as for enzyme deficiencies and to reveal clinical features of CAH patients. Method: The files of a total of 145 patients, admitted, and monitored in our clinic between January 1998 and January 2018 with a diagnosis of CAH were retrospectively analyzed. Age, admission complaints, gender, clinical diagnoses of the patients, development of precocious puberty, and hypertension, presence of testicular adrenal rest tumor, hormonal evaluation results were recorded. Results: Eighty-two female, and 63 male patients were included in the study. All patients had been raised in accordance with their genetic sex. The 21-hydroxylase deficiency was detected in 87.6% of the patients, while 80.9% of them were of classical (76.3% salt-wasting, 23.7% simple virilizing) and 19.1% of them were of non-classical type. Nine percent of the cases had 11?-hydroxylase, 2.8% of them 3?-hydroxysteroid dehydrogenase and 0.7% of them POR deficiency. Consanguineous marriage was detected in 73.8% of the cases. A 70.7% of the female patients were diagnosed with ambiguous genitalia and 73.0% of the male patients with salt- losing type. Fifteen patients were treated with GnRH analogues due to central precocious puberty. Testicular adrenal rest tumor was present in 14.3% of the male cases and polycystic ovary syndrome in 9.8% of female cases. Hypertension was present in nearly half of the cases with 11?-hydroxylase deficiency. The only patient with POR deficiency was diagnosed with Antley-Bixler Syndrome based on her syndromic features. Conclusions: The frequency of enzyme deficiencies seen in patients with CAH in our center was consistent with the literature. Patients without any evidence of mutation suggesting 21-hydroxylase deficiency but have clinical, and syndromic features resembling hypertension, and relevant hormonal clues should be reevaluated as for the rare forms of CAH.
Distribution of enzyme deficiencies in patients with congenital adrenal hyperplasia: A single-center experience with 145 patients
Keywords: Konjenital Adrenal Hiperplazi; 21-Hidroksilaz Eksikliği; Enzim; Congenital Adrenal Hyperplasia; 21-Hydroxylase Deficiency; Enzyme